Convergence of titles to insurance Social Security - Brzeziński, Artur (The use of atypical forms of employment in violation of labour and social security laws - diagnosis and prospects for the future, 2023)
There is no doubt when determining what type of social insurance a given person is subject to, if we are dealing with employment that is the only source of income, i.e. employment under an employment contract, running one’s own business, performing work on the basis of a mandate contract, etc. The problem arises when a given person receives income from several different sources at the same time, e.g. he or she is also an employee employed under an employment contract and runs his or her own business, or is a retiree, works and additionally runs a business. Convergence of insurance rights occurs when one person simultaneously meets the condition for being covered by the obligation to insure under at least two titles. Insured persons whose basis for calculating retirement and disability insurance contributions due to employment, membership in a cooperative, service, receiving training benefits, social benefits per month is lower than the minimum remuneration for work – are also subject to compulsory social insurance for other reasons – art. 9 section 1a of the act on social insurance. The basis for calculating contributions is not subject to conversion if the employment contract is performed on a part-time basis, with the remuneration set at an amount lower than the minimum wage. A person employed by several different employers under different employment contracts is obligatorily subject to all social insurance and health insurance for the performance of each of these contracts. The issues mentioned in this study become particularly important in the context of possible violations of the law related to the use of atypical forms of employment. Incidentally, this is the main topic of my monograph. Problems also arise when there is an incorrect determination of intentional or unintentional coincidence of titles in the context of social insurance, or when the obligation relationship is constructed in such a way as to artificially generate convergence of titles to insurance. This is an extremely important issue that has potential legal consequences and consequences for participants of the social security system. This reflection raises questions about the need for precise legal regulation and monitoring of such situations in order to prevent abuses and violations of the law in the area of employment and social security. Research and analysis in this area are crucial to developing a more effective and adequate legal framework that can adapt to changing labor market realities and ensure fairness and transparency in social security systems, social protection.